Cytokine imbalance in irritable bowel syndrome: a systematic review and meta‐analysis. Issue 7 (5th May 2014) - Bashashati, M.; Rezaei, N.; Shafieyoun, A.; McKernan, D. P.; Chang, L.; Öhman, L.; Quigley, E. M.; Schmulson, M.; Sharkey, K. A.; Simrén, M.
Abstract Background Irritable bowel syndrome (IBS) is a functional gastrointestinal disorder of unknown etiology; although infection and inflammation have recently been considered as important etiologic agents. A recent meta‐analysis showed correlations between cytokine [interleukin‐10 (IL‐10) and tumor necrosis factor (TNF)] gene polymorphisms and IBS; however, it is still unknown whether patients with IBS have different cytokine profiles compared to healthy population. Methods To determine the relationships between serum/plasma levels or mucosal expression of IL‐10/TNF‐α and IBS, we conducted a systematic review and meta‐analysis based on case–control studies retrieved from PubMed and EMBASE search through August 2013. Standardized mean difference (SMD) was generated by using the inverse variance method. Heterogeneity was assessed based on I2 values. Key Results Serum/plasma levels of TNF‐α tended to be higher in IBS vs controls (p = 0.09); this reached significance in IBS subtypes vs controls and in female patients with IBS. However, serum/plasma levels of IL‐10 were not significantly different in IBS patients vs controls. Further analysis of serum/plasma IL‐10 levels in IBS subtypes did not show any difference; however, analysis based on gender showed a significantly lower serum/plasma IL‐10 levels in male patients with IBS vs male controls (p = 0.02). Colonic IL‐10 mRNA had a significantly lower expression in IBS vs control (p = 0.001). Conclusions & Inferences There is an imbalance of proinflammatory TNF‐α, and anti‐inflammatory IL‐10, cytokines in IBS. Stratifying IBS patients based on cytokine profile may represent an opportunity for personalized treatment of this condition.